RAINBOW CONNECTION AND STRONG RAINBOW CONNECTION NUMBERS OF - Antoro, Srava Chrisdes (Universitas Gunadarma, 2016)
A rainbow path in an edge coloring of graph is a path in which every two edges are assigned different colors. If a nontrivial connected graph contains a rainbow path for every two vertices in , then is rainbow-connected. The rainbow connection number of is the minimum integer such that is rainbow connnected in an edge-coloring with colors. If a nontrivial connected contains a rainbow path geodesic for every two vertices in , then is strongly rainbow-connected. The strong rainbow connection number of is the minimum integer such that is strongly rainbow-connected in an edge coloring with colors. The rainbow connection and strong rainbow connection number of graph , , and have been found. In this paper, the results will be generalized and the rainbow connection and strong rainbow connection number of graph will be determined. Keywords: rainbow coloring, rainbow connection number, strong rainbow coloring, strong rainbow connection number, graph